2016
DOI: 10.1097/jpo.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Four-Session Physical Therapy Program Emphasizing Manual Therapy and Exercise on the Balance and Prosthetic Walking Ability of People with Lower-Limb Amputation: A Pilot Study

Abstract: Purpose: No consensus exists regarding best practice for prosthetic rehabilitation programs after unilateral lower-limb amputation. A program integrating manual therapy with exercise for people using lower-limb prostheses has not been systematically investigated. The objectives of this pilot study were to determine whether a four-session physical therapy program of manual therapy, exercise, and functional training would (1) be feasible for people with lower-limb amputation and (2) produce medium to large effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
(64 reference statements)
0
17
0
1
Order By: Relevance
“…Prior studies have proposed general training recommendations to allow the user to explore and engage the functional capabilities of themselves and the prosthesis 105, 131134 . A review on therapeutic interventions to improve prosthetic gait performance identified five categories: supervised walking, specific muscle strengthening, balance training, (part-to-whole) gait training, and functional mobility training 132 .…”
Section: Motor Performance As a Patient-specific Variable For Desimentioning
confidence: 99%
“…Prior studies have proposed general training recommendations to allow the user to explore and engage the functional capabilities of themselves and the prosthesis 105, 131134 . A review on therapeutic interventions to improve prosthetic gait performance identified five categories: supervised walking, specific muscle strengthening, balance training, (part-to-whole) gait training, and functional mobility training 132 .…”
Section: Motor Performance As a Patient-specific Variable For Desimentioning
confidence: 99%
“…Looking at the protocols and tests, the most commonly found was the Berg Balance Scale, or selected items of the Berg Balance Scale (Figure 2). 14,31,73,80-82,93,94,103,107,118-120,138-140,144,147-168 Timed Up and Go 76,107,117,144,145,148,149,151,162,163,165,169-180 and Limits of Stability tests 12,13,20,25,30,37,42,46,47,59,71,72,74,83,84,89 were common (Figure 2). One leg stance test appeared with various names in about some studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that explicitly stated limitations or confounders were just over two-thirds of the total (Table 2),. 13,14,19–22,24,28–56,71,74,76,77,80–95,108,109,115–132,140–145,147–165,169–180,182–184,188–191,193–198 The most commonly mentioned limitation was small sample size, 20,22,24,28,29,32,33,35,37,39,40,42,45,47,52,54-57,74,80,82,86,87,89,93,95,109,118,119,121,123,126,129,141,143,145,148,149,154-159,161,164,169,172,183,198 followed by generalizability issues, 14,19-21,34,38,41,42,44,52-56,80,81,87,89,109,127-130,142,148,151,155,156,162,171,175-177,184,188,189,191,193,196 recall bias, 14,148,150,157,171,173,182,184 heterogeneous groups, 29,42,54,89,142,174,176,177 homogenous groups, 21,38,39,44,45,91,164 and convenience samples. 14,161,176,177,196…”
Section: Resultsmentioning
confidence: 99%
“…Potential participants were excluded if they could not understand the study description for any reason; had diagnosed medical conditions affecting balance including blindness, vestibular disorders, traumatic brain injury, and hemiplegia; or had medical conditions making exercise dangerous such as uncontrolled hypertension or unstable angina. Planned sample size for the 1-year funding period was 10 participants, based on a past interventional study ( Wong et al, 2016 ), to allow for 50 data collection points.…”
Section: Methodsmentioning
confidence: 99%